Protecção integrada em tomate de indústria: estimativa do risco de lagarta do tomate Helicoverpa armigera - Mexia, António (2009)
In Portugal, the processing tomato is of great economical importance. The objective of the work carried out in the Ribatejo is to develop an IPM program, particularly to establish risk assessment methodologies and decision rules for the main enemies of the tomato crop. Of these main enemies the fruitworm (Helicoverpa armigera (Hbn)) is the key-pest. The method that is in validation is based on the techniques used in California and México. These methods allowed to reduce sprays and change to alternative control methods, in particular biological ones - Bt and Trichogramma pretiosum releases. This study presents the research fields, main targets and results during 2000 crop season. Risk assessment methodologies are described and presented the adopted decision rules. A study related with egg and parasitized egg’s spatial distribution on the plant and on the field. Eggs were preferentially on superior level, inferior foliar page, terminal leaflet and field quadrants near the passes. Parasitized eggs do not follow this pattern. It is also presented natural parasitism level and discussed the value of adults monitoring curve as a quantitative risk assessment method.